Psychology of the deaf person: some considerations - Figueroa Pozo, Hilda (2003)
In this article we present some concepts associated to psychical problematic and behavior of the deafness, trying to remark some aspect of the sign language understood as a natural and fundamental way of the psychological development of deaf people, without resting importance to the transcendent and enrichening experience of the education in oral language. Finally, we give emphasis in the right of all people to choose the way to communicate. Likewise, this article makes certain precisions about some researches that were made in our country related to sign language.